Provisional Agenda for the Sixteenth Meeting of the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2007)
The following is the provisional agenda for the Sixteenth Meeting of the International Monetary and Financial Committee, which is to be convened on Saturday, October 20, 2007, at the Fund's Headquarters in Washington, D.C.